Youth Assets and Initiation of Sexual Intercourse by Family Structure: A Longitudinal Cohort Study. (December 2022) - Sanchez, Louisiana M.; Oman, Roy F.; Yang, Yueran; Lensch, Taylor; Clements-Nolle, Kristen
Background: The purpose of this study was to assess the protective influence of individual, family, and community assets from the initiation of sexual intercourse (ISI) for adolescents living in one-parent households compared with adolescents living in two-parent households. Methods: Five waves of data were collected annually over a 4-year period ( N = 591, 52.5% female, mean age = 14.0 years) from a racially/ethnically diverse sample of adolescents. Extended Cox models were used to assess the relationship between assets and time of ISI while controlling for demographic variables. Potential interactions between adolescent's household structure and assets were examined. Results: Five of 17 assets were prospectively and significantly associated with a reduced risk of ISI among adolescents living in one-parent households compared with 11 of 17 assets for adolescents living in two-parent households. Adolescents living in one-parent households who possessed any one of five assets (e.g., general aspirations for the future, relationship with mother, positive peer role models) had between a 27% and 57% lower risk of ISI, whereas adolescents living in two-parent households who possessed any of one of 11 assets (e.g., responsible choices, family communication, community involvement) had between a 20% and 42% lower risk of ISI. Conclusion: The results suggest that strengthening specific youth assets across multiple dimensions of behavioral influence may decrease the risk of ISI for adolescents living in both one-parent and two-parent households. Public health efforts focused on developing programs to promote asset building tailored to adolescent's family structure are warranted.